Perubahan Sosial dalam Upacara Adat Perkawinan Pada Etnis Batak Toba di Tapanuli Bagian Utara (Analisis Sosiologis) - Harisan Boni Firmando (Lembaga penelitian dan pengabdian kepada Masyarakat, 2021)
The traditional wedding ceremony of the Toba Batak ethnicity is a sacred activity and is a hereditary heritage carried out to this day. Currently, there are several changes in the implementation of traditional wedding ceremonies after the Batak Toba people in their hometown have interacted with people from other areas. The existing customary rites have begun to change, this change has given birth to a new habit. The purpose of this study was to determine the social changes in the traditional wedding ceremony of the Toba Batak ethnic group in Tapanuli Bahagian Utara. This research uses qualitative methods with data collection techniques, observations, interviews, document studies and focus group discussions. The results of this study found that the implementation of a series of stages in the traditional wedding ceremony that is currently taking place has progressed where the existing customs have become more diverse. The occurrence of this new habit is caused by various things, namely the influence of the teachings which the majority of the Batak Toba people adhere to, the changing space and time, and the actualization of status and power to achieve life goals. Various strategies are carried out by agents to achieve life goals by changing existing structures. This change in structure can be seen in changes in the way the traditional rituals are carried out which are organized repeatedly, in which various practices of traditional wedding ceremony rites are produced and reproduced, so that they continue to exist. Along with various developments, the implementation of traditional wedding ceremonies will experience challenges, namely consumerism, materialism and declining solidarity. However, this challenge is not a barrier to maintaining the traditional wedding ceremony.